The British trade union delegation in Georgia (according to bolshevist newspapers in Georgia) - Foreign Bureau of the Social-Democratic Workers Party of Georgia (Paris, 1924)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: Tweede Internationale (1889-1919).; onafhankelijkheid; Georgië